Role of non‐coding RNAs in head and neck squamous cell carcinoma: A narrative review. (3rd November 2017) - Sannigrahi, MK; Sharma, R; Panda, NK; Khullar, M
Abstract : Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide with high recurrence, metastasis, and poor treatment outcome. Recent studies have reported that non‐coding RNA (ncRNA) might play critical role in regulating different types of cancer. MicroRNAs (miRs) are short ncRNAs (20–25 nucleotides) responsible for post‐transcriptional regulation of gene expression and may have a role in oncogenesis by acting as oncomiRs or tumor suppressor miRs. Long non‐coding RNAs (lncRNAs) are heterogenous group of ncRNAs more than 200 nucleotides long, can act in cis and/or in trans, and have been also implicated in carcinogenesis. These molecules have been suggested to be promising candidates as diagnostic and prognostic biomarkers and for development of novel therapeutic approaches. In this review, we have summarized recent findings on role of these ncRNAs in HPV‐negative (HPV−ve) and HPV‐positive (HPV+ve) HNSCC. The available literature supports differential expression of both microRNAs and long non‐coding RNAs, which include oncogenic ncRNAs (miR‐21, miR‐31, miR‐155, miR‐211, HOTAIR, and MALAT1) and tumor suppressor ncRNAs (let7d, miR‐17, miR‐375, miR‐139, and MEG3) in HPV+ve HNSCC tumors as compared to HPV−ve tumors and they have distinct role in the pathophysiology of these two types of HNSCCs.